Game Physics Pearls - Bergen, Gino van den; Gregorius, Dirk (A K Peters/CRC Press, 2010)
Implementing physical simulations for real-time games is a complex task that requires a solid understanding of a wide range of concepts from the fields of mathematics, physics, and software engineering. The chapters cover topics such as collision detection, particle-based simulations, constraint solving, and soft-body simulation. The contributors write based on their experience in developing tools and runtime libraries either in game companies or middleware houses that produce physics software for games on PCs and consoles.